2022
DOI: 10.1542/hpeds.2021-006250
|View full text |Cite
|
Sign up to set email alerts
|

“Help Me Sleep”: A Quality Initiative to Reduce Overnight Vital Signs

Abstract: BACKGROUND AND OBJECTIVES Sleep is an essential part of the recovery process, yet inpatient sleep quality is poor. Patients and families report that vital signs are the most bothersome overnight disruption. Obtaining vital signs every 4 hours (Q4H) is not evidence-based and is frequently ordered indiscriminately. We aimed to decrease the percentage of patient nights with vital sign checks between 12 am and 6 am in a low-risk population from 98% to 70% within 12 months to minimize overnight sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Others have conducted QI interventions intending to minimize unnecessary disruptions to sleep. 7,10,[13][14][15] Cooke et al, 7 Lee et al, 13 and Lin et al 14 similarly targeted overnight vital sign orders; however, Cooke et al only targeted blood pressure, while Lee et al targeted blood pressure and temperature measurement (in addition to laboratory collection timing). Lin et al limited the study population to pediatric patients hospitalized with failure to thrive or hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Others have conducted QI interventions intending to minimize unnecessary disruptions to sleep. 7,10,[13][14][15] Cooke et al, 7 Lee et al, 13 and Lin et al 14 similarly targeted overnight vital sign orders; however, Cooke et al only targeted blood pressure, while Lee et al targeted blood pressure and temperature measurement (in addition to laboratory collection timing). Lin et al limited the study population to pediatric patients hospitalized with failure to thrive or hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%
“…24 Promising quality improvement work in a children's hospital showed that overnight vital signs could be safely decreased by 60% in a low-risk patient population without any adverse events. 25 A second major challenge described by participants related to the limitations of the hospital room. Although nurses were quick to acknowledge that no patient expects their hospital room to resemble a "Hilton hotel," they pointed to poor soundproofing in all rooms, and insufficient or excess light exposure depending on the room.…”
Section: Discussionmentioning
confidence: 99%
“…Among adult SCT patients, data have suggested that less rigorous monitoring of vital signs for lower‐risk patients may be safe and simultaneously allow for more uninterrupted time for those recovering after SCT 24 . Promising quality improvement work in a children's hospital showed that overnight vital signs could be safely decreased by 60% in a low‐risk patient population without any adverse events 25 …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the positive results seen in this and similar studies at other sites suggest this approach may be applicable across pediatric health systems. 6,[11][12][13]…”
Section: Limitationsmentioning
confidence: 99%